Public satisfaction on the green facilities of eco malls in Malaysia / Nurhafiza Hasin - Hasin, Nurhafiza (Faculty of Architecture, Planning and Surveying, 2013)
This research was carried out to determine public satisfaction on the green facilities. The green initiatives have made responsible parties ways by creating new methods to be implemented in shopping mall. The developers and owners have taken steps to create sustainable shopping centers by implementing “greener” methods into the building facilities. Therefore, to achieve the aim of this research which is to analyze public satisfaction on green facilities in eco malls, the case study buildings selected are eco malls Space U8 at Taman Bukit Jelutong, Seksyen U8 and Setia City Mall at Setia Alam, Shah Alam. This eco malls buildings were designed to showcase technologies that will reduce the building energy consumption and cost saving. The questionnaire and interview survey were conducted on 40 respondents of each case study. The respondents consist of the tenants, and the visitors in the building. Observation indicated the both of the eco mall implement several types of green facilities to conserve energy use. Finally, the study reveal most of the respondents are acknowledge about energy saving green facilities. Moreover, the LED digital signage is the best recommendation for building users that can be install at the both eco malls. The LED digital signage can show how to use correct way of green facilities features, With relation to the title, the main purpose of this study is to evaluate public perceptions and to recommend ways to improve user’s satisfaction on eco malls.